The influence of extrinsic and intrinsic parameters on the quality of cottage cheese - Modise, Kelepile Dorcas Tebello (Bloemfontein: Central University of Technology, Free State, 2014)
Cottage cheese is a product of drained fresh cheese curd with a mild acidic flavour. The texture can be chunky or smooth; and in South Africa, cottage cheese comes in flavoured varieties that include biltong, chives, garlic and herbs. Although cottage cheese is a nutritious dairy product, it is prone to spoilage by Pseudomonas spp., Staphylococcus spp., Listeria spp., Escherichia coli, Candida spp. and Debaryomyces spp. amongst others. Spoilage of cottage cheese may occur due to several contamination of: cleanliness of equipment surfaces used during production, airborne microbes within the environment, hygiene practices of food handlers, and the quality of water used during production. Here is, however, only limited information available with regard to contamination in the production of cottage cheese in South Africa. This study focused on the assessment of bioaerosols (airborne microbes) in a typical cottage cheese manufacturing facility, the organic acid profile changes during storage at refrigeration and room temperatures, and the knowledge, practices and behaviour of factory workers in relation to food hygiene in cottage cheese factories. Matrix Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI TOF MS) was used to identify bacteria and fungi down to species level from equipment surfaces and bioaerosols. High Pressure Liquid Chromatography (HPLC) was further used for the identification of organic acids found in cottage cheese during shelf life. Lastly, questionnaires and an observational checklist were used for gathering data from food handlers during the study. Bacterial counts isolated from equipment surfaces utilised during the production of cottage cheese ranged between 0.8 x 103 cfu.cm-2 and 2.8 x 102 cfu.cm-2, with fungal counts ranging between 0.5 x 102 cfu.cm-2 and 1.6 x 102 cfu.cm-2. The bacterial counts from bioaerosols (from the production, packaging, shrink wrap and pasteurization areas) ranged between 72 cfu.m-³ and 92 cfu.m-³ counts with average fungal counts of 53 cfu.m-3 and 58.5 cfu.m-3. Microbes isolated included species from genera Staphylococcus, Lactobacillus, Bacillus, Pseudomonas, Candida, Micrococcus, Enterobacter and Acinetobacter amongst others. Staphylococcus aureus in dairy products such as milk, yoghurt and cheese have been reported to cause foodborne disease outbreaks. These species were isolated from equipment, including the moulded cheese container before and after salting. Lactobacillus spp. are known to be associated with milk products and Lactobacillus coryniformis, Lactobacillus lactis and Lactobacillus mali were isolated from cheese vat 1, cheese vat 4 and the cheese scale. Lactobacillus lactis ssp. cremoris and Lactobacillus lactis ssp. lactis are mainly used in the production of cottage cheese as they have the ability to utilise milk citrate to produce characteristic flavour compounds. Bacillus cereus on the other hand was isolated from cheese vat 4 while Bacillus pumilus and Bacillus licherniformis were isolated from the cheese scale. The presence of Bacillus cereus in undercooked meat products and unpasteurized milk has been reported to cause foodborne disease outbreaks. Bacillus licherniformis and Bacillus pumilus are not human pathogens nor toxigenic, although they have been implicated in the spoilage of dairy products. As far as it could be determined, this is the first report of the isolation of Pseudomonas spp., Staphylococcus spp., Candida spp., Lactobacillus spp. and Acinetobacter spp. from bioaerosols in the cottage cheese section of a dairy plant. Cottage cheese samples were stored at 4°C and at a room temperature of 27°C to determine their spoilage rates and to assess the type and quantity of organic acids within the cottage cheese. Spoilage of cottage cheese may result if improper refrigeration conditions and the wrong starter cultures are used during production stages. From the second week of sampling, test results from cottage cheeses showed that the pH of the cottage cheese sample stored at 4°C was slightly higher (pH 4.25) than that of the cottage cheese sample stored at room temperature 27°C (pH 4.15). Spoilage of cottage cheese occurred from week 3 for cottage cheese stored at 27°C. Results obtained from HPLC on organic acids in cottage cheese samples stored at 4°C and 27°C confirmed the presence of oxalic, orotic, citric, lactic, acetic, fumaric and uric acids. Formic, acetic, butyric and propionic acids are volatile acids, contributing to the aroma of cottage cheese. Questionnaires and an observational checklist were used to gather information from the food handlers in the cottage cheese section of a dairy plant. During the production of cottage cheese it was observed that 60% of the food handlers used their bare hands (put their hands inside cheese vats) to feel if the curd was cooked to a desired state. Cross-contamination of cheese may originate from cheese vats, cheese cloth, production room air, floor surfaces, packaging material, starter cultures, brine and curd cutting knives. Thirty percent of food handlers admitted to not cleaning the manufacturing equipment after use. Insufficient sterilization of equipment surfaces remaining damp after sanitization allows the attachment of spoilage and pathogenic organisms leading to contamination. Contamination of cottage cheese due to improper food handling practices and poor hygiene status of the cottage cheese section could lead to its spoilage. Results from this study indicate that bioaerosols, the hygiene practices of food handlers, and microbial contaminants from equipment surfaces influence the spoilage potential of cottage cheese. There is currently a lack of agreed standards on bioaerosols in the food sector worldwide. Lack of data may cause under-estimation of the spoilage potential of bioaerosols, and there is therefore a need for agreed standards worldwide.
Thesis
Keywords: Cottage cheese - Microbial contamination; Cottage cheese - Storage; Chromatographic analysis; Food handling; Cottage - Processing